Influence of soil microplastic contamination and cadmium toxicity on the growth, physiology, and root growth traits of Triticum aestivum L. - Iqbal, Babar; Javed, Qaiser; Khan, Ismail; Tariq, Muhammad; Ahmad, Naveed; Elansary, Hosam O.; Jalal, Arshad [UNESP]; Li, Guanlin; Du, Daolin (Elsevier, 2023)
Cadmium toxicity in the soil severely threatens many native ecosystems, including plant communities. Microplastic (MP) accumulation in agricultural ecosystems constitutes a problem due to the fact that it stresses crops as well as lowers their production. On the other hand, it has yet to be apparent how MP pollution and Cd toxicity affect crops. In this instance, wheat plants subjected to polyethylene MP contamination, Cd toxicity, and a combined treatment were used in a greenhouse setting to assess above- and below-ground crop features related to stress responses utilizing root scan and leaf gas exchange studies. Changes in root characteristics, a decrease in leaf gas exchange, and phenological indices were among the consequences that were noticed. Regarding below- and above-ground features, MP pollution was the treatment that had the fewest negative effects, whereas cadmium toxicity along with soil MP contamination had the worst effects. Additionally, Cd toxicity and interaction treatment lowered root area and width, while MP pollution enhanced all belowground variables. Combined treatment with MPs and Cd toxicity reduced phenological indices, leaf gas exchange, and belowground root traits compared to control. These insights raise concerns regarding potential yield, economic losses, and consequences of a possible transport into the food web.
Keywords: Cadmium toxicity; Leaf gas exchange; Plant phenology; Root growth traits; Soil microplastics contamination; Triticum aestivum L.